Exosomal ANGPTL2 in cerebrospinal fluid as a novel prognostic biomarker for primary central nervous system lymphoma - Zhu, Lili; Li, Qing; Ma, Jingjing; Xu, Huiwen; Ma, Yan; Lin, Zhiguang; Zhang, Mengxue; Wang, Songmei; Wang, Xuanyi; Chen, Bobin (Frontiers in Immunology, 2026)
BackgroundAngiopoietin-like protein 2 (ANGPTL2) functions as a key pro-tumorigenic mediator in the tumor microenvironment. While liquid biopsies using exosomal proteins to reflect tumor phenotypes and progression are well established for extracranial cancers, their use in primary central nervous system lymphoma (PCNSL) remains unexplored. Therefore, this study aimed to assess the potential of exosomal ANGPTL2 in cerebrospinal fluid (CSF) as a prognostic biomarker for PCNSL.MethodsWe retrospectively reviewed the medical records of patients newly diagnosed with PCNSL at our institution from May 2020 to September 2023. Using enzyme-linked immunosorbent assay (ELISA), we measured CSF exosomal ANGPTL2 levels in 78 patients with PCNSL. Patients were divided into high- and low-level groups based on the median. The Kaplan–Meier analysis with a log-rank test was used to compare survival rates between groups. Univariate analysis was used to identify prognostic factors, and multivariate Cox proportional hazards regression was used to determine the independent predictors of PCNSL outcomes.ResultsThe median level of CSF exosomal ANGPTL2 was 4.410 ng/mL. Patients with high CSF exosomal ANGPTL2 had significantly shorter progression-free survival (PFS; p = 0.001) and overall survival (OS; p = 0.003). The complete response (CR) rate was 33.3% in the high-level group versus 66.7% in the low-level group (p = 0.003), and the overall response (OR) rate was 35.9% versus 74.4% (p = 0.001).ConclusionCSF exosomal ANGPTL2 is a novel, independent prognostic marker in PCNSL.